Performance analysis of direct detection optical OFDM systems - D, Kumar; R, Anilkumar; C N, Vijayakumar; Bhargavi, S (International Journal of Engineering and Technology, 2018)
Orthogonal frequency division multiplexing (OFDM) is a multicarrier modulation technique, in which the data information is carried over many lower rate subcarriers. This technique is started effectively using in both line communication and wireless communication systems. This modulation technique has been actively started in the field of light wave communication called optical OFDM (OOFDM) system. OOFDM is a multicarrier modulation technique; it is used to overcome the problem of inter-symbol interference due to the chromatic dispersion and polarization mode dispersion of the fiber channel. In this paper, we have done simulation on direct detection optical OFDM (DDOOFDM) system with data rate of 10Gbps and measuring performance analysis of DDOOFDM system with respect to the received optical power and various full width half maximum value of the continuous wave laser source. This analysis is simulated using RSOFT Design Group OptSim Version-5.2.